UK AFV and PPV procurement using Urgent Operational Requirements (UOR) - Antill, Peter D.; Smith, Jeremy C. D.; Moore, David M. (Cranfield University, 2012)
Peter D Antill, Jeremy CD Smith and David M Moore explain how the Ministry of Defence rushed through a set of urgent solutions to provide better protection for deployed personnel travelling in Armoured Fighting Vehicles (AFVs) and Protected Patrol Vehicles (PPVs) in Iraq and Afghanistan.